2021
DOI: 10.31235/osf.io/fcqd9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of COVID-19 on Fertility behaviour and Intentions in the Republic of Moldova

Abstract: The COVID Pandemic could affect fertility behaviour and intentions in many ways. Restrictions on service provision may reduce access to family planning services and increase fertility in the short term. By contrast, the economic uncertainty brought about by the pandemic and its impact on mental health and well-being may reduce fertility. These various pathways have been explored in the context of high income countries such as the United States and Western Europe, but little is known about middle income countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Against the previous discussion on the role of economic uncertainty during recessions and on the Italian context, a reduction in fertility can be expected. Studies on Italy and on other developed countries have already shown some evidence of that (Cohen 2021, Li et al 2021Lindeberg et al 2020, Guetto et al 2020, Micelli et al 2020, Blangiardo 2021, while studies on low and medium-income countries (Emery andKoops 2021, Zhu et al 2020) found mixed effects of the pandemic on fertility intentions. In Italy, first data released by ISTAT 8 shows that, compared to the same months of the previous year, in December 2020 the number of births declined by 10.3%; this is the first month in which the effects of the first epidemic wave are observable.…”
Section: The Impact Of the Covid-19 Pandemic On Births And Fertility Intentionsmentioning
confidence: 98%
“…Against the previous discussion on the role of economic uncertainty during recessions and on the Italian context, a reduction in fertility can be expected. Studies on Italy and on other developed countries have already shown some evidence of that (Cohen 2021, Li et al 2021Lindeberg et al 2020, Guetto et al 2020, Micelli et al 2020, Blangiardo 2021, while studies on low and medium-income countries (Emery andKoops 2021, Zhu et al 2020) found mixed effects of the pandemic on fertility intentions. In Italy, first data released by ISTAT 8 shows that, compared to the same months of the previous year, in December 2020 the number of births declined by 10.3%; this is the first month in which the effects of the first epidemic wave are observable.…”
Section: The Impact Of the Covid-19 Pandemic On Births And Fertility Intentionsmentioning
confidence: 98%
“…In 2021, the TFR (1.73) decreased by just 0.03 births per woman compared to 2020 (1.76). This may be because contraceptive usage fell by around 40% among couples with and without medium-term fertility intentions (Emery and Koops, 2021).…”
Section: Impact Of Fertility On Depopulationmentioning
confidence: 99%
“…Studies on Italy and on other developed countries have shown mixed evidence of a possible fertility reduction (in intentions and behaviours) due to the pandemic [ 3 , 4 , 20 – 22 , 46 , 76 – 80 ], as in low and medium-income countries [ 81 83 ].…”
Section: The Impact Of the Covid-19 Pandemic On Births And Fertility ...mentioning
confidence: 99%